Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4+2]-Cycloaddition reaction with arynes as dienophiles - Pandya, Virat G.; Mhaske, Santosh B. (Tetrahedron Letters, 2022)
A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[f]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N-Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[f]quinoline scaffolds in good to moderate yields.
Keywords: Aryne; Diels-Alder; Diene; Tetrahydrobenzo[ f ]quinoline